Calcium sulfate and PTFE nonporous barrier for regeneration of experimental bone defects - De Macedo, Nelson Luiz [UNESP]; De Macedo, Luís Guilherme Scavone [UNESP]; Monteiro, Adriana Do Socorro Ferreira [UNESP] (My University, 2008)
The aim of the study was to evaluate the possibility to obtain guided bone regeneration with two types of physical barriers (calcium sulfate and PTFE nonporous barrier) in surgical defects created in rat parietal bones. In the right parietal bone the calcium sulfate barrier filled out the whole defect and in the left parietal bone the barrier of PTFE was positioned in the floor and externally to the surgical defect. After 7, 14, 30 and 45 days four animals were sacrificed in each period and the bone containing the defects were submitted to the microscopic analysis. The results of the study revealed that the PTFE barrier was more effective for bone regeneration in shallow transcortical defects compared to the calcium sulfate. However, additional experiments are necessary to determine if calcium sulfate would be successful in other bone defects types or the use of the material under another consistence could complement the results obtained in this work. © Medicina Oral S. L. C.I.F.
Keywords: Artificial membranes; Bone regeneration; Bone substitutes; Calcium sulfate; Guided tissue regeneration; Polytetrafluoroethylene